Amino‐Functionalized Multilayer Core–Shell Mesoporous Organosilica Nanospheres for Cr(VI) Removal. Issue 18 (3rd July 2018) - Lai, Xin; Sun, Dan; Hou, Yi; Zuo, Yi; Li, Yubao; Zhang, Li
Abstract: Developing low‐cost and highly efficient adsorbents for the removal of toxic heavy metal ions is the subject of intensive research with the increasingly stringent water pollution control standards. In this paper, three types of amino‐functionalized multilayer core–shell mesoporous organosilica nanospheres (MCMONs) are synthesized using an indirect cocondensation method for Cr(VI) removal applications. Results show that amino groups are successfully immobilized on the nanospheres and these amino‐functionalized MCMONs exhibit unique organic–inorganic multilayer core–shell structures. When used as adsorbent for Cr(VI) removal, the N‐(3‐trimethoxysilylpropyl)diethylenetriamine functionalized MCMONs exhibit a maximum adsorption capacity of 279.92 mg g −1 at initial Cr(VI) concentration of 150 mg L −1 . This is about 20% greater than the highest Cr(VI) adsorption capacity previously reported for other core–shell silica‐based adsorbents, demonstrating the great potential of MCMONs in Cr(VI) removal applications. Abstract : Three types of amino‐functionalized multilayer core–shell mesoporous organosilica nanospheres (MCMONs) with different surface density of amino functions are synthesized for Cr(VI) removal. The N‐(3‐trimethoxysilylpropyl)diethylenetriamine functionalized MCMONs exhibit a maximum Cr(VI) adsorption capacity of 279.92 mg g −1, which is about 20% greater than the highest adsorption capacity of the previously reported core–shell silica‐based adsorbents.